Historical roots of pain management in infants: A bibliometric analysis using reference publication year spectroscopy - Kanwaljeet J. S. Anand; Jean‐Michel Roue; Cynthia R. Rovnaghi; Werner Marx; Lutz Bornmann (Wiley, 2020)
Abstract Retrospective evaluations of the historical role of previously published research are often fraught with subjective bias and misrepresentation, which leads to contested scientific claims. This paper investigates the historical roots of infant pain management using novel quantitative methods to identify the published literature and evaluate its relative importance. A bibliometric analysis named "reference publication year spectroscopy" (RPYS), was performed using the program CitedReferencesExplorer (CRExplorer) to avoid the subjectivity associated with comparative evaluations of individual research studies. Web of Science (WoS) search queries on infant‐related synonyms, pain‐related synonyms, and analgesia or anesthesia‐related synonyms were combined using the Boolean operator "AND," to identify all publications related to pain management in infants. The RPYS analyses were based on 8697 papers in our publication set containing the citations for 86268 references. Selected cited publications were associated with peak citation years in 1951, 1954, 1957, 1965, 1987, 1990, 1997, 1999, and 2000. Subsequent analyses suggested that research on infant pain management made rapid progress during 1982‐1992. Landmark publications were defined as those belonging to the top 10% of the most frequently referenced publications for longer than 25 years. Through this analysis, we identified and ranked 24 landmark publications to illustrate the historical background and early research on infant pain management. From the first‐ever application of RPYS (an objective, reproducible approach to study the early history of any scholarly activity) to pain research, infant pain management appears rooted in the scientific rationale for neonatal pain perception, randomized trials of opioid anesthesia/analgesia, and studies describing the facial expressions and crying activity following heel‐lance procedures in newborns.